Syphilis: an unusual manifestation?. (19th September 2014) - Bezalely, Shai; Jacob, Giris; Flusser, Gideon; Ablin, Jacob
Abstract : Syphilis is a widely investigated infectious venereal disease with varied presentations frequently mimicking other diseases. It progresses in distinct, well-characterised stages: early (primary and secondary), latent, and late (tertiary), each stage having its own unique presentations. However, there has been increasing evidence of atypical presentations. We describe one such presentation of early syphilis in its secondary stage. A man in his late 20s presented with a rash (which is typical of the secondary stage) and with bone pain with multiple lytic lesions (which is rare in the secondary stage but more typical of the tertiary stage). The patient was successfully treated for secondary syphilis. On the basis of our case, and on analysis of other case reports and research of early-stage syphilitic bone involvement, we conclude that the true incidence of bone involvement in early-stage syphilis may be higher than has been previously appreciated, and thus may be under-recognised and underdiagnosed.